Warnock 40 Years on: The Development of Special Educational Needs Since the Warnock Report and Implications for the Future - Lindsay, Geoff; Wedell, Klaus; Dockrell, Julie (Frontiers in Education, 2020)
The report of the Warnock Committee ‘Special Educational Needs, published in 1978, provided the first comprehensive review of special educational needs (SEN) in England and the basis for subsequent legislation, from the Education Act 1981 to the recent Children and Families Act 2014. The Warnock Report has been highly influential with respect to the development of both national and local policy and practice for SEN, primarily in England but also in the UK generally and internationally. We conceived the ‘Warnock 40 Years On’ research topic published in this journal as an opportunity to examine developments for children and young people with SEN or a disability (SEND) since the Report’s publication. As editors of this research topic, in this paper we provide an overview of major elements within SEND, drawing on both the individual constituent papers and the broader policy and research literature. We examine the origins and precursors of the Warnock Review, including then current progressive conceptual development and practice, leading to an examination of the Review. We explore the legislative structure arising from the Report and implementation of the SEND system - from the Education Act 1981 onwards. We critically examine a number of key aspects of the Warnock Report and how these developments of the SEND system have taken these forward, including: categorisation of SEN; provision made to meet the special needs of children and young people with SEN or a disability, including inclusion; early identification and intervention; the important rights and role of parents; prevalence of different types of SEN and the complex interaction between SEN and a range of factors, including social disadvantage and ethnicity; and a range of SEND research. Finally we consider the implications for future development of the SEND system, in particular whether its limitations can be addressed better by ‘patching up’ the system or by ‘system change’. Although focused on England, this paper has relevance - as did the Warnock Report – to SEND internationally.